The Administrator’s Leadership and High-Performance Organization of school under Samutsongkhram Primary Educational Service Area Office - Sitthipongsakul, Bunthita; Intarak, Prasert (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
This article aimed to study (1) the school administrator’s leadership under Samutsongkhram Primary Educational Service Area Office; (2) the school’s high-performance organization under Samutsongkhram Primary Educational Service Area Office; and (3) the relationship between the administrator’s leadership and the high-performance organization of the school under Samutsongkhram Primary Educational Service Area Office. The sample consisted of 63 schools under the Samutsongkhram Primary Educational Service Area Office. The three respondents from each school consisted of a school director or acting school director, a deputy director or head of personnel division, and a teacher, with a total of 189. The research instrument was an opinionnaire regarding an administrator’s leadership, based on the concept of Kouzes and Posner, and a high-performance organization, based on the concept of Blanchard. The statistics used for data analysis were frequency, percentage, arithmetic mean, standard deviation, and Pearson’s product–moment correlation coefficient. It was found that: 1) the school administrator’s leadership under the Samutsongkhram Primary Educational Service Area Office as a whole was at the highest level. The arithmetic mean ranking from the highest to the lowest was as follows: encourage the heart, inspire a shared vision, enable others to act, model the way and challenge the process; 2) The school high performance organization under Samutsongkhram Primary Educational Service Area Office as a whole was at the highest level. The arithmetic mean rankings from the highest to the lowest were as follows: shared information and open communication, relentless focus on customer results, energizing systems and structures, ongoing learning, shared power, high involvement, and compelling vision; and 3) The relationship between the administrator’s leadership and the high-performance organization of school under Samutsongkhram Primary Educational Service Area Office was high correlation, with significantly at .01